Both Prayed to the Same God Religion and Faith in the American Civil War. - Miller, Robert J. (Lanham : Lexington Books, 2007)
Both Prayed to the Same God offers a popular yet scholarly overview of the most-ignored aspect of the American Civil War_the absolutely crucial role that religion played before, during, and after this deadliest of American wars. This fascinating book outlines how religion and faith paved the way to division, were the greatest forces maintaining wartime morale, and helped shape forever how America's Civil War would be remembered.
13 Through a Moral Lens-DarklySection Four: Churches and Religion after the Civil War; 14 ""Lost Cause"" Religion; 15 Putting a Misconception to Death?; 16 The Greatest Wartime Theologian; 17 Religious Consequences of the Civil War; Author's Note; Appendix: Religious Affiliations; Select Bibliography; Index; About the Author.
Description based on print version record.
Keywords: United States -- History -- Civil War, 1861-1865 -- Religious aspects; United States -- Religion -- 19th century; United States -- History -- Civil War, 1861-1865 -- Religious aspects; HISTORY / United States / State & Local / General; Electronic books